DORNER, Daniel G., GORMAN, G.E. and CALVERT, Philip, J. Information needs analysis: principles and practice in information organizations. London: Facet. 2015. 269 pages. ISBN: 978-1-85604-484-4. (2015) - Hughes, Emma
No abstract available